2014
DOI: 10.1055/s-0033-1338640
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Structure Classification of Heteraspiro[m.n]alkanes

Abstract: The fundamental spirane framework consists of two monocyclic rings linked in an orthogonal relationship by a common ring atom. In spiranes with no annular heteroatom, four carbon atoms are bonded directly to the quaternary spirocarbon. The spirocarbon may be the site of a stereogenic centre and stereoisomerism. This review covers families of spiranes where one or both rings carry additional annular heteroatoms, mainly N, O or S. The heteroatoms are indicated by replacement prefixes. In general, the term 'heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…Spirocyclic compounds are molecules containing two rings linked by a common C atom (spiroatom). Since the discovery of this class of compounds, it has been found that similar structures exist in many natural and synthetic products (Smith & Baxendale, 2015;Undheim, 2014). Spirocyclic compounds containing a chiral spiro-quaternary C atom are especially attractive to organic chemists (Galliford & Scheidt, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Spirocyclic compounds are molecules containing two rings linked by a common C atom (spiroatom). Since the discovery of this class of compounds, it has been found that similar structures exist in many natural and synthetic products (Smith & Baxendale, 2015;Undheim, 2014). Spirocyclic compounds containing a chiral spiro-quaternary C atom are especially attractive to organic chemists (Galliford & Scheidt, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…7 We recently published a review on heteraspiranes with annular heteroatoms where no heteroatom is directly attached to the quaternary spirocarbon. 8 The most recent report deals with α-monoheteraspiranes where one heteroatom is directly bonded to the spirocarbon. 9 The present review deals with families of tri(α-hetera)spiranes where the three heteroatoms (O, S or N) are directly bonded to the spirocarbon.…”
Section: Introductionmentioning
confidence: 99%
“…A review was published in 2014 on heteraspiranes with annular heteroatoms where no heteroatom is directly attached to the quaternary spirocarbon. 1 This review discusses families of α-monohetera-spiranes where one heteroatom is directly bonded to the spirocarbon. One or both spirane rings may contain additional annular heteroatoms (N, O, S) without direct bonding to the carbon center.…”
Section: Introductionmentioning
confidence: 99%